Analysis Of The White Lily Metaphor As A Representation Of Inner Conflict In جندي يحلم بالزنابق البيضاء Mahmoud Darwish’s Poem - Sabrina Azzindani Putri; Misbahus Surur (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2025)
This article analyzes Mahmoud Darwish’s poem جندي يحلم بالزنابق البيضا through Viktor Shklovsky’s concept of defamiliarization within the framework of Russian Formalist theory. The poem reveals the inner conflict of a weary soldier who dreams of peace symbolized by the white lily. Using a qualitative descriptive approach, this study explores how Darwish’s poetic language—rich in metaphors, paradoxes, and imagery—transforms conventional meanings of purity and heroism into reflections on trauma, loss, and existential struggle.The white lily, which traditionally represents innocence and peace, becomes a contradictory symbol bridging beauty and suffering, life and death. The findings indicate that Darwish employs defamiliarization techniques to challenge familiar discourses of nationalism and war, compelling readers to reinterpret universal concepts such as “homeland” and “victory” in more personal and human terms. Ultimately, Darwish’s aesthetic strategy not only deepens the reader’s emotional engagement but also encourages critical reflection on the human condition amid conflict.